ANALISIS PENYUSUNAN ANGGARAN PADA CV. BUANA RAYA MEDAN - ARWIN .; WILLIAM LIUS; SISKA MEDIYANTI; RINA FRISKA BR SIAHAAN; TASIK UTAMA (LP2MTBM MAKARIOZ, 2019)
A budget is a periodic financial plan that covers a company's operational activities within a certain period. Budgeting is theprocess of operating a plan in the form of qualifications, which are usually in monetary form, for a certain period of time. Witha good budget, the company can arrange planning the amount of income desired from the results of its business, the amountof expenses, and profits to be achieved in a period. The formulation of the problem in this study is